Controle modal ótimo de um rotor flexível utilizando atuadores piezelétricos do tipo pilha - Simões, Ricardo Corrêa (2006)
This work deals with active vibration control of flexible rotors. Vibratory control behavior of a horizontal rotor containing two disks and suported by bearings on its extremities was studies numericaly and experimentaly. Numerical simulations was perfomaded using Finite Element Method (FEM). The target control was to atenuate the vibration of first 4 bending modes by using of a Linear Quadratic Regualdor. A modal method was required to reduce the model size and make the model controllable. A state observer estimated the modal state coordenates necessary to model method. The control forces were applied over the structure by piezeletric stack actuators. These actuators were orthogonally arranged in control plane locatted in one of bearings bearings of the rotor. The experimental identification of stiffness of active bearings compoments and MEF model ajust was carrifully conducted. The sucsses of metholody was intrically related to this work part, that has allowed the accured calculation of the contol force. Experiments were carried out in a rotor test rig. Optimal modal Controller performance has been tested to various operation conditions and differents excitation forces, like rotor at rest, steady state rotation and transiente rotation. Numerical and experimental results attest the sucsses of control strategy and shows the potentiality of stack piezelectric actuators in the active vibration control to rotordynamics field.